Assessment of Differential Renal Function in Children with Hydronephrosis: Comparison of DMSA and MAG-3 - ŞEKERCİ, ÇAĞRI AKIN; ŞİMŞEK, FERRUH; ALPAY, HARİKA; TARCAN, TUFAN (GALENOS YAYINCILIK, 2015)
Objective Nuclear imaging techniques such as 99mTc-dimercaptosuccinic acid (DMSA) and (99)mTc-mercaptoacetyltriglycine (MAG-3) are widely used for the diagnosis and follow-up of urinary tract obstructions. Both imaging techniques provide the differential renal function (DRF) in slightly different ways. The aim of this study was to assess the MAG-3 scan as an adjunct or alternative to DMSA for evaluating DRF in children with hydronephrosis. Materials and Methods Eighty-one patients with hydronephrosis were enrolled in this study. Patient age, sex, anteroposterior renal pelvis diameter (RPD) at the time of diagnosis, parenchymal thickness and the DRF percentage found by both DMSA and MAG-3 were recorded. DMSA scintigraphy was used for detecting renal scars and estimating DRF. MAG-3 scintigraphy was used for evaluation of renal clearance, the collecting system's outflow pattern and estimating DRF. Results A total of 102 renal units (38 left, 22 right and 21 bilateral) were evaluated. High correlation rates were found when we compared both tests' DRF values according to antero-posterior renal pelvic diameter and patient age (p>0.05). In all groups compared in the present study, both tests demonstrated very similar results and DRF values. Statistical analysis of cut-offs (45%, 40%, 10%) were also similar in both methods (p>0.05, kappa > 0.7, r=0.926 Pearson). Conclusion DMSA and MAG-3 are tests that are of assistance in the evaluation of hydronephrosis. Compared to DMSA, MAG-3 also provides valuable information to evaluate DRF values in hydronephrotic renal unit (RU). Avoiding unnecessary DMSA imaging will save time and cost and prevent over-radiation of the pediatric population.
Keywords: Kidney; hydronephrosis; MAG-3; DMSA; differential function; children